Can pimozide kill parasites? Surprisingly, the most honest answer is ‘yes’ - Georgia Marquez-Grap; Allison Kranyak; Nicholas Brownstone; John Koo (Journal of Dermatological Treatment)
ABSTRACT Purpose: One of the most well-known medications for treating delusional infestation (DI) is pimozide. Many patients may be reluctant to initiate treatment unless a medication has anti-pathogenic properties, as they feel otherwise it does not address their concerns regarding infestation. In this article, we explore the evidence that pimozide has a range of antipathogenic effects and how this fact can aid in patient care.Materials and methods: A scoping literature review was performed using The National Library of Medicine (PubMed). The search terms used were pimozide AND anti-microbial OR anti-bacterial OR anti-infective. All relevant articles were reviewed up to September 2024.Results: Our findings show that pimozide has antibacterial and antiparasitic effects through several unique mechanisms. Additionally, several older first-generation antipsychotics also have demonstrated anti-pathogenic properties. While the studies identified are entirely in vitro, the potential antipathogenic effects of pimozide may be pivotal to patients with DI as they make the critical decision to accept or reject treatment.Conclusion: With adequate disclaimers that pimozide’s therapeutic efficacy may not have to do with its anti-pathogen profile, the evidence that pimozide has anti-pathogenic properties may enable dermatology providers to strengthen their therapeutic approach and alliance with patients with DI and make life-changing therapy more acceptable to the patient.